Studi Komparatif tentang Kemandirian pada Anak Usia Taman Kanak-Kanak Ditinjau dari Ibu Bekerja dan Tidak Bekerja - Miftahul Jannah; Ifani Candra (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2020)
This study aims to determine the differences in independence of kindergarten-aged children in terms of working and nonworking mothers in the kindergartens over Talawi district, Sawahlunto sity. This research is a type of comparative research. The variable used in this study is independence. The sampling technique uses random sampling where samples from the population were carried out randomly without regard to strata that exists in the population. The sample of this study was 161 kindergarten children consisting of 49 working mothers and 112 non-working ones. The data collection method uses children's independence scale. The results of the study based on statistic calculations which were obtained a mean value of 111,69 for non-working mothers and 101,65 for working ones. Calculation of Independent Sample t-Test is obtained t-count> t-table (3,934> 1,975) and P value (0,00 <0,05), then Ho is denied, so it can be concluded that there are significant differences in the level of independence of kindergarten-aged children referred to working and non-working mothers in the kindergartens over Talawi district, Sawahlunto city